Women water guardians and their participation in communitarian management. An analysis of the Ecuadorian normative - Martínez-Moscoso, Andrés (2020)
The recognition of water as a human and fundamental right in Ecuador, implied countless challenges, including the incorporation of the gender approach in community management of water resources. This necessity has been acknowledged in the law, as well as in public policies, although in practice there is still a gap in the real participation of women due to persistent gender roles that exclude them from the decision making process. This paper develops a normative study, from international human rights instruments to Ecuadorian legislation regarding the incorporation of the human right to water, as well as the implementation of a gender perspective in water management. It also includes case studies, which show that active, free and meaningful participation of women in these communitarian systems is not yet fully achieved. After this analysis and the following discussion, the work concludes that the integration of women in management and decisionmaking of communitarian water committees, is not only done by eliminating physical, but also social barriers to participate, which could prevent women from having a leading role within their communities, in an active and passive form.